Identificação das proteínas diferencialmente expressas nos hemócitos de populações de Biomphalaria tenagophila (Orbigny, 1835) (Gastropoda: Planorbidae) suscetível e resistentes a Schistosoma mansoni Sambon 1907 (Trematoda: Schistosomatidae) - Ivana Helena Rocha Oliveira (2015)
Schistosomiasis mansoni remains one of the main parasitic diseases in the world and is caused by a trematode of the species Schistosoma mansoni, whose invertebrate hosts are molluscs of the genus Biomphalaria. Biomphalaria tenagophila is an important host in Brazil, with some strains being highly susceptible to the parasite, whereas others are absolutely resistant to infection. The nature of the resistance and susceptibility of B. tenagophila is not completely understood, but it is assumed that the hemocytes, effector cells of molluscs internal defense system, play a crucial role in controlling trematode infections. Thus, the study of proteins produced by hemocytes in response to infection by S. mansoni can generate relevant contributions to a better understanding of host-parasite interaction. This study compared the proteomic profiles of hemocytes from the hemolymph of resistant B. tenagophila populations (Taim / RS and Anchieta / ES) and a susceptible one (Cabo Frio / RJ), challenged or not with S. mansoni. Through the two-dimensional electrophoresis and DIGE the protein profiles of the three populations before and after challenge were evaluated and then differentially expressed proteins were identified by mass spectrometry. The findings showed proteins with altered expression between resistance and susceptibility phenotypes, especially after exposure to S. mansoni. In the Taim challenged population, it was observed an elevation of two relevant proteins: a member of the thioester-containing proteins (TEP) family, which is related to phagocytosis or encapsulation of pathogens; and a hypothetical protein LOTGIDRAFT_234865 involved in binding and transport of a product of reactive oxygen species formation. Increased HSP70 and fructose-bisphosphate aldolase expression in Cabo Frio challenged may be related to this strain susceptible phenotype. The absence of the complete B. glabrata genome affected proteins identification and database analysis. Nevertheless, results were significant and confirmed the already known complexity of the molecular interaction between Biomphalaria and S. mansoni.